Association Between Sleep Duration and Anxiety in US Adults: A Nationally Representative Cross-Sectional Study - Wang X; Zhong Y; Wang R; Zhang D; Li Y; Pan Y; Li Y (Psychology Research and Behavior Management)
Xing Wang,1 Yunhui Zhong,2 Rui Wang,3 Dongdong Zhang,4 Yihan Li,5 Yi Pan,1 Yibo Li6 1Huzhou Third Municipal Hospital, the Affiliated Hospital of Huzhou University, Huzhou, 313000, People’s Republic of China; 2The Third People’s Hospital of Ganzhou, Ganzhou, 341000, People’s Republic of China; 3Department of Psychiatry and Psychotherapy, University of Tübingen, Tübingen, 72076, Germany; 4School of Medicine, Xiamen University, Xiamen, 361100, People’s Republic of China; 5Faculty of Health and Wellness, City University of Macau, Macao, 999078, People’s Republic of China; 6Institute of Medical Psychology and Behavioral Neurobiology, University of Tübingen, Tübingen, 72076, GermanyCorrespondence: Yibo Li, Email yiboli.psy@outlook.comBackground: Previous studies on the relationship between sleep duration and anxiety have yielded inconsistent results. This study aimed to explore this association using data from a large, nationally representative sample of US adults.Methods: Data from 13,476 participants in the National Health and Nutrition Examination Survey (NHANES) 2007– 2012 were analyzed. Weighted robust Poisson regression models were employed to assess the relationship between sleep duration and anxiety, with additional subgroup analyses conducted to explore variations across different demographic groups.Results: Among participants, 25.8% exhibited symptoms of anxiety. Compared to normal sleep duration (7– 9 hours), very short sleep durations (< 5 hours) and short sleep durations (5 to < 7 hours) were significantly linked to higher anxiety risks, with adjusted incidence rate ratios (IRRs) of 1.40 (95% CI [1.23– 1.59]) and 1.17 (95% CI [1.09– 1.25]), respectively. Subgroup analyses revealed that shorter sleep durations were more strongly associated with anxiety in males, older adults, racial minorities, and married individuals compared to their counterparts. Notably, long sleep duration (≥ 9 hours) showed no significant overall association with anxiety (IRR = 1.11 [0.95– 1.29]); however, in specific subgroups such as non-married individuals and younger adults, it was linked to an increased risk of anxiety.Conclusion: Short sleep duration is associated with an increased risk of anxiety, with the strength of this association differing notably across demographic subgroups. Long sleep duration is associated with higher anxiety risk exclusively in specific groups, including non-married individuals and younger adults. Further research is needed to uncover the mechanisms underlying these associations.Keywords: sleep duration, anxiety, NHANES, mental health, cross-sectional study